Barrier Analysis and Needs Assessment of the Policy Environment for Agriculture in Nine CARICOM Countries - Hayman, Alicia A (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
It has bibliographic references on pages 39-45